2022
DOI: 10.3350/cmh.2021.0314
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir alafenamide treatment may not worsen the lipid profile of chronic hepatitis B patients: A propensity score-matched analysis

Abstract: Background/Aims: Tenofovir alafenamide (TAF) has a less favorable effect on lipids compared to TDF (Tenofovir disoproxil fumarate) in clinical trials. However, data regarding these outcomes in patients with chronic hepatitis B (CHB) are scarce.Methods: This study is to evaluate the effects of TAF on the lipids of 237 CHB patients, compared with TDF, inactive CHB, and non-HBV infected control groups, using propensity score-matching (PSM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
(55 reference statements)
3
18
0
Order By: Relevance
“…As reported, TAF might not worsen the lipid profiles in either non‐HBV‐infected controls andnor in patients with inactive chronic hepatitis B in a real‐world setting 5 . In this study, patients who switched to TAF showed a trend of elevated low‐density lipoprotein and triglyceride.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…As reported, TAF might not worsen the lipid profiles in either non‐HBV‐infected controls andnor in patients with inactive chronic hepatitis B in a real‐world setting 5 . In this study, patients who switched to TAF showed a trend of elevated low‐density lipoprotein and triglyceride.…”
supporting
confidence: 58%
“…[2][3][4] As reported, TAF might not worsen the lipid profiles in either non-HBV-infected controls andnor in patients with inactive chronic hepatitis B in a real-world setting. 5 In this study, patients who switched to TAF showed a trend of elevated low-density lipoprotein and triglyceride. These changes in lipid profile, especially in patients who were switched from TDF-containing treatment, may be caused by the removal of lipid-lowering effect of TDF.…”
mentioning
confidence: 57%
“…At present, antiviral therapy is considered to be a main means to delay the progression of chronic HBV infection. As a first-line drug for the treatment of chronic HBV infection, the tenofovir disoproxil fumarate (TDF) could mediate antiviral, antiproliferative, and immunomodulatory effects; however, its efficacy is limited in less than half of subjects treated, and the underlying reason is still vague [5][6][7]. Therefore, the immunological mechanism of chronic hepatitis B (CHB) patients who responded or nonresponded to antiviral therapy needs further evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Jeong et al [ 5 ] applied propensity score-matching to compare the changes of lipid profile among CHB patients receiving TAF or TDF, inactive CHB, and non-HBV infected control groups in a follow-up period of 48 weeks. The results showed a significant decrease of serum total cholesterol (TC) level in the TDF group when compared with TAF (156.7±27.7 vs. 176.3±32.9, P <0.001) and non-HBV infected (156.2±28.3 vs. 175.0±29.5, P <0.001) group.…”
mentioning
confidence: 99%
“…Jeong et al [ 5 ] further postulated that the higher circulating tenofovir concentration in TDF users than that in TAF users might explain the results. Their theory was supported by another paper from Canada in which lower lipids were observed in TDF group when compared with the entecavir group in CHB patients [ 6 ].…”
mentioning
confidence: 99%